Does the Use of Ozone as a Cavity Disinfectant Affect the Bonding Strength of Antibacterial Bonding Agents? - Cangul, Suzan; Erpacal, Begum; Adiguzel, Ozkan; Sagmak, Savas; Unal, Server; Tekin, Samet (Taylor & Francis Inc, 2020)
The aim of this study was to evaluate the use of ozone as cavity disinfectant on the bonding strength to dentin of different antibacterial bonding agents. The study was conducted on 60 cavity-free 3rd molar teeth. The prepared samples were separated into 3 groups. These groups were each sub-divided into 2 groups of 10 as a group with ozone applied and a control group. In Group 1a, ozone was applied as cavity disinfectant for 6 secs to all the exposed dentin surfaces then restoration was applied. In Group 1b as the control group, the restoration stages were applied without any cavity disinfection. Gluma 2 Bond, our first antibacterial adhesive material, was applied to all dentin surfaces and polymerized. The second and third groups were divided into two groups. Clearfil SE Protect Primer and Clearfil SE Protect Bond were applied in the group 2. Peak Universal was used in Group 3. After the application of the adhesive materials and then Estelite posterior quick composite was applied and polymerized. The bonding strengths of all the samples were measured in an Instron test device. The data were statistically analyzed using the Mann Whitney U-test and the Kruskal Wallis test. The highest bonding strength was determined in Gluma 2 Bond (7,79), and the lowest bonding strength was in Peek Universal (3,43). It was concluded that ozone adhesive systems can be safely currently used as they have been shown to increase bonding strength and can eliminate bacteria.
Keywords: Ozone; antibacterial; bond; cavity; disinfectant; bond; strength; test; device